Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1475-2875-11-396
|View full text |Cite
|
Sign up to set email alerts
|

Foetal haemoglobin and the dynamics of paediatric malaria

Abstract: BackgroundAlthough 80% of malaria occurs in children under five years of age, infants under six months of age are known to have low rates of infection and disease. It is not clear why this youngest age group is protected; possible factors include maternal antibodies, unique nutrition (breast milk), and the presence of foetal haemoglobin (HbF). This work aims to gain insight into possible mechanisms of protection, and suggest pathways for focused empirical work, by modelling a range of possible effects of foeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The present results also fail to compare with conclusions from a study in Mali in which an age stratified analysis showed sickle trait-mediated malaria protection to be more evident in early childhood [ 39 ]. Possible explanations for the lower incidence of uncomplicated malaria among HBB wild types in the current study could relate to protection conferred by fetal hemoglobin and maternal antibodies during early childhood [ 40 42 ]. However the present study did not assess for the levels of fetal haemoglobin and maternal antibodies in infancy, thus other studies would be needed to confirm this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The present results also fail to compare with conclusions from a study in Mali in which an age stratified analysis showed sickle trait-mediated malaria protection to be more evident in early childhood [ 39 ]. Possible explanations for the lower incidence of uncomplicated malaria among HBB wild types in the current study could relate to protection conferred by fetal hemoglobin and maternal antibodies during early childhood [ 40 42 ]. However the present study did not assess for the levels of fetal haemoglobin and maternal antibodies in infancy, thus other studies would be needed to confirm this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…One might assume an intensive use of bed nets in that age group but there was no difference according to the use of ITNs within age groups. In younger children, especially under six months old, the presence of maternal antibodies may decrease the prevalence of PI and therefore of asymptomatic infection [ 53 , 54 ], while in older infants, over six months, when maternal protection wanes, asymptomatic infection may be uncommon as the lack of acquired anti-malaria immunity deviates these children immediately to symptomatic or even severe symptomatic malaria episodes, decreasing the prevalence of asymptomatic infection in these infants [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of in-vitro malaria parasite growth inhibitory characteristics of lactoferrin and immunoglobin A (IgA) found in breast milk as well as maternal and infant sera has led others to hypothesize that infants are protected from malaria [8,9]. The assumption of infant's immunity against malaria was further boosted by studies that showed that high hemoglobin F concentration at birth inhibits malaria parasite's development in the first few months of human life [10,11]. This assumption of a sixmonth period of protection in a newborn in contradicted by other studies which found no relationship between presence of maternal antibodies and their protection against malaria in African infants [11,12].…”
Section: Discussionmentioning
confidence: 99%